Підготовка майбутніх соціальних працівників до роботи з людьми з особливими потребами в процесі професійно орієнтованої практики - Равлюк, Тетяна (My University, 2014)
The importance of future social workers training is proved, the principles of its organization are characterized (the theoretical knowledge and practice, consistency, continuity, polyfunctionality, prospect, independence, activity, initiative, etc.), approaches (the system, an integrated, software variant, individually-creative, student-focused, etc.) to the organization of different types of praxis (introductory, voluntary, preventive, educational-technological, trainee, predegree) in the context of social support and care for people with special needs are described in the article. Specificity of continuous professional-oriented praxis facilitates the formation of future specialists skills of interaction with the people with special needs in various forms of assistance and system of methods; and the formation of professionally significant personal qualities, as well as the creation of conditions for the development of creativity
Keywords: people with special needs, professionally oriented praxis, introductory, voluntary, preventive, educational-technological, trainee, predegree praxis of future social workers